DIGITAL STORYTELLING: AS A NEW-GENERATION CREATIVE TECHNOLOGY IN LEARNING ENGLISH (SCIENCE TIME JOURNAL, 2026)
Digital storytelling has emerged as one of the most promising creative technologies in English language teaching, as it integrates narrative construction, multimedia tools, and learner-centered production within a single pedagogical framework. Unlike conventional language exercises that prioritize reproduction, digital storytelling positions students as authors, speakers, designers, and presenters of meaning. Research consistently demonstrates that this approach advances speaking fluency, vocabulary acquisition, pronunciation, motivation, collaborative skills, and digital literacy. Notably, digital storytelling bridges language practice with twenty-first-century competencies, including creativity, critical thinking, communication, and technological proficiency. This article examines the pedagogical foundations of digital storytelling, its advantages for English language education, the methodological stages of classroom implementation, and its applicability across school and university contexts.